The awareness of Islamic banking products and services among non-Muslim students in University Sains Malaysia - Ali, Khalil Ismail (2019)
Islamic banks have shown a positive growth that attracts many scholars, investors, and clients globally. In Malaysia, it has been almost three decades when the first Islamic bank makes its debut. Islamic banks have to compete with its conventional banks which have longer history than Islamic banks. Malaysia, one of the pioneer members of this emerging banks is also experiencing notable development in operating more than seventeen Islamic banking institutions. However, non-Muslim clients experienced difficulties when it comes to understanding of overall system, principles, features and sophisticated Arabic terms that Islamic banks use. This study examined the level of awareness, understanding and perceptions among the Non-Muslim’s students of USM on Islamic banking products and services. Data was collected using hand delivery questionnaire survey approach. Using non probability sampling, two hundred and sixty (260) Non-Muslim USM students’ respondents were selected to participate in this study. For the analysis, one-way ANOVA and Pearson Correlation Coefficient was adopted to analyse the results. The result revealed that most of the non-Muslim students in USM are not aware with some of the Islamic banks products and services. The study further found that although there is no significant relationship between understanding and awareness, a positive correlation between understanding of Islamic bank product and awareness among the non-Muslims students of USM exist. Also, the result showed that there is positive significant relationship between perception of Islamic bank product and its awareness among the non-Muslims students of USM. Moreover, the study found that demographic factors such as gender, age, religion, and level of education show no significant differences among respondents. This study provides theoretical and managerial implications for the Islamic bankers to attract non-Muslims customers and recommendations for future research in Islamic Banking. The managerial implication of this study is for the Islamic banking industry and managers should take all necessary steps to adopt marketing policies and other endeavours in order to make sure that all clients of Islamic banks understand the benefit of Islamic banking products, positive perception towards the Islamic banking products and services, and should have a maximum awareness of all the Islamic banking products and services.